Theoretical and legal characteristics of the civil law principles - О. О. Kolobylina (Bulletin of Kharkiv National University of Internal Affairs)
It has been noted that the purpose of the principles of law is to ensure a uniform formulation of legal norms and their impact on social relations in the form of legal regulation and other forms of legal influence. They identify ways to improve legal provisions and act as guiding ideas for legislators. When enshrined in legal acts, principles ensure the unity of the processes of creating, implementing and protecting law.